Efforts of Ward Head Nurses in Optimizing Nursing Care Management through Workload Management and Effective Communication among Nursing Teams - Lesmana, Nevi Kuspiana (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This study explores the efforts of ward head nurses in optimizing nursing care management, focusing on workload management and effective communication within nursing teams. Utilizing a qualitative research design and a literature review methodology, this study synthesizes relevant scholarly sources from 2015 to 2025. The findings highlight the critical role of ward head nurses in balancing the distribution of workloads and ensuring clear communication to enhance the overall quality of care. Effective workload management leads to reduced nurse burnout, higher job satisfaction, and better patient outcomes, while effective communication reduces errors, fosters collaboration, and improves team morale. The research underscores the importance of leadership strategies that integrate both workload and communication management to create a cohesive and efficient nursing team. However, challenges such as staffing shortages, resource limitations, and the integration of digital communication tools remain significant barriers. The study emphasizes the need for organizational support and leadership training to empower ward head nurses in optimizing these strategies. The findings contribute to the growing body of literature on nursing leadership and provide practical insights for healthcare administrators, nursing leaders, and policymakers aiming to improve nursing care management.